Characterization, localization, and sequence of F transfer region products: the pilus assembly gene product TraW and a new product, TrbI. - Maneewannakul, S (1992)
The traW gene of the Escherichia coli K-12 sex factor, F, encodes one of the numerous proteins required for conjugative transfer of this plasmid. We have found that the nucleotide sequence of traW encodes a 210-amino-acid, 23,610-Da polypeptide with a characteristic amino-terminal signal peptide sequence; in DNA from the F lac traW546 amber mutant, the traW open reading frame is interrupted at codon 141. Studies of traW expression in maxicells in the presence and absence of ethanol demonstrate that the traW product does undergo signal sequence processing. Cell fractionation experiments additionally demonstrated that mature TraW is a periplasmic protein. Electron microscopy also showed that F lac traW546 hosts do not express F pili, confirming that TraW is required for F-pilus assembly. Our nucleotide sequence also revealed the existence of an additional gene, trbI, located between traC and traW. The trbI gene encodes a 128-amino-acid polypeptide which could be identified as a 14-kDa protein product. Fractionation experiments demonstrated that TrbI is an intrinsic inner-membrane protein. Hosts carrying the pOX38-trbI::kan insertion mutant plasmids that we constructed remained quite transfer proficient but exhibited increased resistance to F-pilus-specific phages. Mutant plasmids pOX38-trbI472 and pOX38-trbI473 expressed very long F pili, suggestive of a pilus retraction deficiency. Expression of an excess of TrbI in hosts carrying a wild-type pOX38 plasmid also caused F-pilus-specific phage resistance. The possibility that TrbI influences the kinetics of pilus outgrowth and/or retraction is discussed.